UAV - Red Green Blue (RGB) Orthomosaic from Röbäcksdalen Drone area 03 - Röbäcksdalen Field Research Station (Swedish University of Agricultural Sciences, 2021)
Near-ground RGB orthomosaics collected from UAV platforms, by means of RGB cameras containing red, green and blue bands. Nominal pixel resolution is 5 cm.
Röbäcksdalen Field Research Station (2021). UAV - Red Green Blue (RGB) Orthomosaic from Röbäcksdalen Drone area 03, 2020-09-07 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/XxKNxlitJ93C4wXbP4y_vUAX
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap